Asymptomatic non-ulcerative genital tract infections in a rural Ugandan population. Issue 6 (December 1998) - Paxton, L A; Sewankambo, N; Gray, R; Serwadda, D; McNairn, D; Li, C; Wawer, M J
Abstract : OBJECTIVE: To document the prevalence of asymptomatic non-ulcerative genital tract infections (GTI) in a rural African cohort. METHODS: The study population consisted of all adults aged 15-59 residing in 56 rural communities of Rakai District, southwest Uganda, enrolled in the Rakai STD Control for AIDS Prevention Study. Participants were interviewed about the occurrence of vaginal or urethral discharge and frequent or painful urination in the previous 6 months. Respondents were asked to provide blood and a first catch urine sample. Serum was tested for HIV-1. Urine was tested with ligase chain reaction (LCR) for N gonorrhoeae and C trachomatis. Women provided two self administered vaginal swabs; one for T vaginalis culture and the other for a Gram stained slide for bacterial vaginosis (BV) diagnosis. RESULTS: A total of 12, 827 men and women were enrolled. Among 5140 men providing specimens, 0.9% had gonorrhoea and 2.1% had chlamydia. Among 6356 women, 1.5% had gonorrhoea, 2.4% had chlamydia, 23.8% were infected with trichomonas and 50.9% had BV.53% of men and 66% of women with gonorrhoea did not report genital discharge or dysuria at anytime within the previous 6 months. 92% of men and 76% of women with chlamydia and over 80% of women with trichomonas or BV were asymptomatic. The sensitivities of dysuria or urethral discharge for detection of infection with either gonorrhoea or chlamydia among men were only 21.4% and 9.8% respectively; similarly, among women the sensitivity of dysuria was 21.0% while that of vaginal discharge was 11.6%. For trichomonas or BV the sensitivity of dysuria was 11.7% and that of vaginal discharge was 10.5%. CONCLUSION: The prevalence of non-ulcerative GTIs is very high in this rural African population and the majority are asymptomatic. Reliance on reported symptoms alone would have missed 80% of men and 72% of women with either gonorrhoea or chlamydia, and over 80% of women with trichomonas or BV. To achieve STD control in this and similar populations public health programmes must target asymptomatic infections.